Pengembangan Aplikasi Belajar Online Berbasis Web Menggunakan Waterfall - Afif Wijang Wahid Ramadhan; Dhoifullah Dhoifullah; Husen Husen; Candra Candra; Sri Mulyati (Program Studi Teknik Informatika Universitas Pamulang, 2021)
In this pandemic era, face-to-face learning cannot be done because the transmission of the virus is very dangerous and after all learning activities must continue, to improve the quality of education in Indonesia, therefore in this sophisticated era we must make the best use of technology for the wrong teaching and learning activities. the only way is by holding it online, but not all schools carry out learning activities with technology, there are still many who do conventional learning such as learning activities in school. The benefit of implementing online learning methods is to make it easier for teachers and students in terms of learning activities. The analysis method used is literature study. design methods that do use the concept of software engineering.